PROBLEMATIC OF AUTONOMY REVIEW OF THE COVID-19 VACCINATION INFORMED CONSENT - Ervin Dyah Ayu Masita Dewi; Hwian Christianto (Universitas Airlangga, 2023)
Background: Not all public approval to receive COVID-19 vaccination is based on understanding the right information, which is considered insufficient motivation. It is also related to inadequate government policies. Aims: This study was to identify the implementation of informed consent in COVID-19 vaccination, in terms of the autonomy of the vaccine recipients, so that the necessary policy could be recommended. Methods: The research was conducted at Surabaya in June-December 2021 with descriptive qualitative methods through in-depth interviews with five vaccinators and five vaccine recipients using purposive sampling. Data were analyzed from interview transcripts by coding, making categories and themes, and then compared to relevant references. Results: The results showed that 60% of the implementation of the COVID-19 vaccination informed consent was inadequate. It was found that incomplete information disclosure is often not even given information, and vaccinations are carried out without a signature of informed consent. These findings suggest that respect for the autonomy of COVID-19 vaccine recipients has not been made. Conclusion: Inadequate respect for the autonomy of vaccine recipients risks causing a medical conflict in the future if there are unexpected effects. Thus, the government must make standard informed consent procedures for COVID-19 vaccination and collaborate with the local government. Keywords: Covid-19 vaccination, informed consent, information disclosure, respect for autonomy